The incarnation of the symbolic codifying symbolic reparation rights in Philippine Law notes (Philippine Law Journal, 2021)
As a country with more than a century of a colonial past, a distant memory of war injuries, a notorious history of dictatorship, and a continuing story of struggling democratic and republican systems, the Philippines ought to have already grasped the concept of restorative justice as transcending not only in the material sense, but all the more so in political, social, cultural, and moral aspects. With its stories of suffering and resiliency, the Philippines is Smaierpatoncanbeachereduswithdierecogrtorof nuanced stakeholder human rights experiences that differ greatly and deeply. Unfortunately, quite the contrary is reflected in its legal system. This Note explores the current application, or the lack thereof, of symbolic reparation in Philippine law. Here, the author assesses the symbolic reparation efforts of the Philippine govemment in three particular incidents: The burial of Dictator Ferdinand Marcos at the Libingan ng mga Bayani, the removal of the Comfort Woman statue, and the repatration of the Balangiga Bells, to ascertain the necessity for a codification of symbolic reparation rights for victims and their families'. The Note concludes in the affirmative-that there exists a necessity for the codification of such rights within the gaping hole of symbolic reparation in Philippine law.